MONOGENEAN PARASITES AND HISTOPATHOLOGY ON HUMPBACK GROUPER (Cromileptes altivelis) IN FLOATING NET CAGES LAMPUNG WATER, INDONESIA - Putri, Septi Malidda Eka; Amiin, Muhammad Kholiqul (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2023)
Humpback grouper (Cromileptes altivelis) is an important commodity in Indonesian. This study aims to report the parasitic humpback grouper worms from eight floating net cages, as well as to observe the histological pathogenesis caused by parasites. May 2019, a total of 80 humpback groupers are used for parasitological and histopathological analysis. Monogenean trematodes Neobenedenia girellae, and Haliotrema epinepheli are found in fish examined. Histopathological analysis showed necrosis, congestion, partial fusion, epithelial hyperplasia, haemorrhage, and telangiectasia. It is important to know monogenean parasites from cultivated fish and pathogenesis caused by parasites to ensure fish production and host health.